Mitigation of off-target toxicity in CRISPR-Cas9 screens for essential non-coding elements - Josh Tycko (Nature Portfolio, 2019)
Off-target effects in CRISPR screens for essential regulatory elements have not been systematically evaluated. Here the authors find Cas9 nuclease, CRISPRi/a each have distinct off-target effects, and that these can be accurately identified and removed using the GuideScan sgRNA specificity score.